Advances in harmonic analysis and operator theory : the stefan samko anniversary volume - Castro, Luis; Speck, Frank-Olme; Almeida, Alexandre (Operator Theory: Advances and Applications, 2013)
This volume is dedicated to Professor Stefan Samko on the occasion of his seventieth birthday. The contributions display the range of his scientific interests in harmonic analysis and operator theory. Particular attention is paid to fractional integrals and derivatives, singular, hypersingular and potential operators in variable exponent spaces, pseudodifferential operators in various modern function and distribution spaces, as well as related applications, to mention but a few. Most of the contributions were originally presented at two conferences in Lisbon and Aveiro, Portugal, in June‒July 2011.